Предмет:
МатематикаАвтор:
buttercupf4ehАвтор:
jamisonb43aАвтор:
braydonbarkerАвтор:
wilberАвтор:
thunder thighsubflОтвет:
Пошаговое объяснение:
2a³ + 3a²b + 3ab² + b³ = a³ + (a+b)³ = (a + a + b)(a² - a(a+b) + (a+b)²) =
= (2a + b)(a² + ab + b²)
Автор:
darbystanleyДобавить свой ответ
Предмет:
Русский языкАвтор:
joseph433Ответов:
Смотреть
Предмет:
Английский языкАвтор:
huntОтветов:
Смотреть
Предмет:
Английский языкАвтор:
irvinОтветов:
Смотреть
Предмет:
Английский языкАвтор:
happyzccpОтветов:
Смотреть